2016
DOI: 10.1111/capa.12170
|View full text |Cite
|
Sign up to set email alerts
|

Policy work at the sub‐national level: Analytical styles of Canadian and Czech directors and managers

Abstract: This paper uses data from two countries to develop profiles of policy directors and managers in the sub‐national public bureaucracies of Canada and the Czech Republic. Canadian directors and managers undertake more analytically complex tasks for which research and evaluation is necessary. In comparison, Czech managers are more firmly engaged in project management agendas, and Czech directors tend to rely on personal experience and routine approaches. Overall, the sample shows that different policy styles are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The problem so far has not been studied in the Czech Republic. An exception is the studies by Veselý (2014) and Nekola and Kohoutek (2016). In other countries, we find a relatively large number of works dealing with similar issues.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The problem so far has not been studied in the Czech Republic. An exception is the studies by Veselý (2014) and Nekola and Kohoutek (2016). In other countries, we find a relatively large number of works dealing with similar issues.…”
Section: Introductionmentioning
confidence: 79%
“…Regarding the Czech Republic, the first investigation of this issue was carried out by Veselý (2014) as part of his research project P404/12/0725 'Analysts of policy in the central government administration of the Czech Republic: practices, professional values and identity'. Other members of the research team of Professor Veselý also contributed to the general understanding of this issue, as well as Nekola, and Kohoutek (2016), Ochrana, Plaček, and Křápek (2015). The second discussion perspective was offered by authors who are dedicated to the problem of policy bureaucracy.…”
Section: Basis Of Examination and Research Questionsmentioning
confidence: 97%
“…In the Czech Republic (and also in the countries of Central and Eastern Europe), this problem is currently being neglected. An exception is the recently published study by Czech authors Veselý (2014) or Veselý et al (2014) and the study by Nekola & Kohoutek (2016), which was devoted, however, to the issue of the government (regions). Their analysis is based on an empirical investigation carried out in the framework of a research project of the Czech Science Foundation Nr.…”
Section: Results Of Examining the Debate The Genesis Of Strategic Govmentioning
confidence: 99%
“…Supervisors, managers, and directors were interviewed based on academic and practical considerations. First, academic discourses have constructed managers as the "missing variable" (Meier, 2009, p. 7; see also Howlett, 2010;Howlett &Walker, 2012) in policy studies, given the observation that they are a relatively understudied group of public administrators (see also Nekola & Kohoutek, 2016;Howlett, 2017). Second, my practical experience as a provincial public servant in PEI showed that the department which was included in the study tended to be involved in projects that required collaborating with staff from across the department's divisions and with other areas of government.…”
Section: Methodsmentioning
confidence: 99%